Modeling farmers’ preference and willingness to pay for improved climate services in Rwanda - Tesfaye, Abonesh; Hansen, James; Kagabo, Desire; Birachi, Eliud Abucheli; Radeny, Maren A.O.; Solomon, Dawit (Cambridge University Press, 2023)
This study aims to understand how Rwandan farmers value the improved characteristics of climate services introduced to them in a choice experiment setting. Data were collected from 1,525 household heads in November 2019. A random parameters logit model was used to analyze the data. Results suggest that Rwandan farmers value forecast accuracy, dissemination through a combination of extension agents and the Participatory Integrated Climate Services for Agriculture process, and bundling with market price information. This study suggests that to improve agricultural management planning and food security of farmers through the provision of climate services, these services need to be accurate, user-tailored, and accessibl